The Cellular and Viral circRNAs Induced by Fowl Adenovirus Serotype 4 Infection - Liu, Xiao-Na; Guo, Xiao-Ran; Han, Ying; Tian, Tian; Sun, Jian; Lei, Bai-Shi; Zhang, Wu-Chao; Yuan, Wan-Zhe; Zhao, Kuan (Frontiers in Microbiology, 2022)
Circular RNAs (circRNAs) are a new class of noncoding RNAs that play vital roles in many biological processes. Virus infection induces modifications in cellular circRNA transcriptomes and expresses viral circRNAs. The outbreaks of Hydropericardium-hepatitis syndrome (HHS) caused by fowl adenovirus serotype 4 (FAdV-4) have resulted in huge economic losses to the poultry industry worldwide. To investigate the expression of circRNAs during FAdV-4 infection, we performed transcriptome analysis of FAdV-4-infected leghorn male hepatoma (LMH) cells. In total, 19,154 cellular circRNAs and 135 differentially expressed (DE) cellular circRNAs were identified. The characteristics of the DE cellular circRNAs were analyzed and most of them were related to multiple biological processes according to GO and KEGG enrichment analysis. The accuracy of ten cellular circRNAs were verified by semiquantitative RT-PCR and sequencing. The change trend was consistent with the RNA sequencing results. Moreover, 2014 viral circRNAs were identified and ten circRNAs were verified by the same methods. Our analysis showed that seven circRNAs with the same 3’ terminal and variable 5’ terminal regions were located at pTP protein and DNA pol protein of FAdV-4 which may be generated via alternative splicing events. Moreover, the expression level of viral circRNAs was closely related to the replication efficiency of the virus and partial of the viral circRNAs promoted the replication of FAdV-4. Competing endogenous RNA analysis further showed that the effects of cellular and viral circRNAs on host or viral genes may act via miRNAs. Collectively, our findings first indicate that FAdV-4 infection induced the differential expression of cellular circRNAs and FAdV-4 also expressed viral circRNAs, some of which affected FAdV-4 replication. These findings will provide new clues for further understanding FAdV-4 and provide a basis for investigating host-virus interactions.